Non-hormonal Pharmacotherapies for Benign Prostatic Hyperplasia: The Role of Tadalafil Monotherapy - Aamir Jalal Al-Mosawi (International Journal of Pharmaceutical & Biological Archive, 2024)
Many medications have been used in the treatment of benign enlargement of the prostate during the 1960s, 1970s, and 1980s, including progestational agents, amino acids, spironolactone, candicidin, nystatin, flutamide, bromocriptine, alpha-adrenergic blockers, Serenoa repens (Saw palmetto extracts), and mepartricin. Finasteride and dutasteride are 5-alpha reductase inhibitors decrease levels of dihydrotestosterone, which contributes to prostate enlargement, have been increasingly used in the treatment of benign prostatic hyperplasia. There is some evidence suggesting that non-hormonal therapies (i.e., medication that do not directly affect male hormones such as testosterone or dihydrotestosterone) can reduce prostate volume, particularly in the context of benign prostatic hyperplasia. In recent years, the use of tadalafil (Phosphodiesterase type 5 inhibitor), as monotherapy for benign prostatic hyperplasia-related lower urinary tract symptoms, has gained increasing attention. Tadalafil has demonstrated potential benefits in improving both the symptoms and the underlying pathology of benign prostatic hyperplasia. The aim of this paper is to highlight the role of tadalafil monotherapy in the treatment of benign prostatic hyperplasia.